Guinea - Speeding up Technology Transfer to Rice Growers - World Bank (Washington, DC, 2012)
In Guinea, improving the productivity of upland rice is a key challenge for the national agricultural services. Though rice is the main staple in Guinea, low yields make the country highly dependent on rice imports that it can ill afford. While the national agricultural research system (Institute de Recherche Agronomique de Guinee, IRAG), did not have improved technology available, the West Africa Rice Development Association (WARDA), located in neighboring Cote d'Ivoire, had made a major breakthrough. It was developing inter-specific rice varieties that combined the best characteristics of the high-yielding Oryza Sativa varieties of Asian origin with those of the hardy Oryza Glaberrima varieties indigenous to Africa. Though the results looked promising, the normal approach of first testing new varieties at research stations and only then releasing them for on-farm trials and then to extension will have taken years. To speed up the process, Guinea's national extension service (Service National de la Promotion Rurale et de la Vulgarisation) teamed up with IRAG in a pilot program that brought promising varieties from WARDA concurrently to evaluations on IRAG stations and to on-farm trials. The participatory pilot program was supported by the World Bank and the Special Program for African Agricultural Research (SPAAR).